Testing for SARS-CoV-2: Can We Stop at 2?. (19th April 2020) - Lee, Tau Hong; Junhao Lin, Ray; Lin, Raymond T P; Barkham, Timothy; Rao, Pooja; Leo, Yee-Sin; Chien Lye, David; Young, Barnaby; ,
Abstract: The COVID-19 epidemic requires accurate identification and isolation of confirmed cases for effective control. This report describes the effectiveness of our testing strategy and highlights the importance of repeat testing in suspected cases in our cohort.